The Icelandic fish export sector : how can Icelandic ground fish producer and exporters reach higher in the value chain? - Ágúst Elvarsson 1984- (2014)
The Icelandic fishing industry in many ways seems to stand at crossroads now. For the past 15 years or so the demand for fish has been more than the supply. Therefore Icelandic fish has been quite easy to sell. With more competition, where Iceland’s main competitors in ground fish production are getting close to the quality of the Icelandic fish and are able to sell it at lower prices. The world is getting smaller and Iceland has competitors they haven’t had to deal with before, countries like China where fish farming of unfamiliar species like tilapia are gaining a lot of market share on the expense of other whitefish species that might be considered more traditional in Iceland. Icelandic fish- producers and exporters have a lot of experience in processing and selling premium quality fish from a sustainable sources. They are mainly selling exporting their products to wholesalers and secondary processor who take the raw material from Iceland and add to the value. Although a lot of the value is created outside of Iceland there is still a significant part of the value created just by catching the fish and portioning it correctly. There are certain trade barriers that stop the producers and exporters to be able to further process the fish in Iceland to export it later. These barriers are mainly distance to market and high transportation costs. Icelandic fish is a premium product and can be sold for quite high prices in the right markets. In some cases it can be sold without too many intermediary parties and therefore for more profit than with the intermediary parties. Closed to protect the identity of interviewees